Faktor Risiko Komplikasi Diabetes Melitus Tipe 2 sebagai Dasar Upaya Pencegahan di Rumah Sakit Islam Malahayati Medan - Mona Hastuti; Rinawati Br Tarigan; Tri Budiarti (Ali Institute of Research and Publication, 2026)
Diabetes mellitus is a non-communicable disease with a steadily increasing number of cases. This increase is due to significant complications that can lead to reduced life expectancy, paralysis, and an increased economic burden. This study aimed to identify risk factors for type 2 diabetes mellitus complications to inform prevention efforts at Malahayati Islamic Hospital in Medan. This observational analytical study used a case-control design. The study population consisted of diabetes patients registered at Malahayati Islamic Hospital in Medan. There were 120 respondents in total, with 60 in the case group and 60 in the control group. Data were collected through direct interviews at the hospital. Univariate and bivariate analyses were used for data analysis. The results showed that patients with diabetes mellitus (DM) for ≥5 years were 7.1 times more likely to develop complications, patients with an obese body mass index (BMI) were 3.9 times more likely to develop complications, patients with irregular blood sugar control were 2.9 times more likely to develop complications, and patients who did not adhere to their medication were 2.3 times more likely to develop complications. Duration of suffering, obesity, irregular blood sugar control, and noncompliance with treatment are risk factors for type 2 diabetes mellitus complications.